Efeito antiinflamatório e antirreabsortivo ósseo do infliximabe na periodontite induzida em ratos Wistar - Gonçalves, Davi da Cunha (2012)
Periodontitis is a chronic inflammatory disease characterized by different levels of collagen, cementum, and alveolar bone destruction. Peridontitis is considered an important cause of tooth loss in adults. Infliximab (Remicade®) is a quimeric monoclonal antibody against the tumoral necrosis factor-alpha (TNF-α) and is currently prescribed in the treatment of the rheumatoid arthritis, Crohn’s disease, psoriasis arthritis, ankylosing spondylitis, and ulcerative colitis. The aim of the current study was to investigate the bone protective effect of infliximab on the experimental periodontal disease (EPD). EPD was induced by passing a 3.0 nylon thread around the upper left second molar in Wistar male rats. Animals were either treated with infliximab (1, 5 e 10mg/kg) or saline solution by endovenous route 30 minutes before the periodontitis induction and were followed until they were sacrificed in the tenth first day. A subset of rats was euthanized in the third day for gingival myeloperoxidase (MPO) and for the neutrophilic MPO index from peripheral blood analyses. We analyzed the following parameters: bone reabsorption markers, including the bone loss index (BLI) by morphometry and periodontal collagen autofluorescence using confocal microscopy, and immunohistochemistry for metalloproteinase-1/-8 (MMP-1/-8) in the maxillary tissue; inflammatory markers, gingival MPO and pro-inflammatory cytokines (IL-1β e TNF-α) detected by western blot and ELISA, leukometry (and complete blood count) and the MPO leukocyte index in the peripheral blood; immune-inflammatory signaling, including immunohistochemistry for RANK, RANK-L and osteoprotegerin (OPG) in the maxillary bone tissue. Experimental periodontitis caused leukocytosis, significant increases in BLI and in pro-inflammatory cytokines with inflammatory cell infiltrate in the gingival tissue and periodontal collagen disarrangement. In the challenged group we also identify various figures of the epithelial cell rests of Malassez (ERM) in the proximity of the cementum and alveolar bone. Infliximab in the dose of 5mg/kg was able to reduce granulocyte numbers in the peripheral blood, improve the BLI and the periodontal tissue collagen integrity and to reduce the inflammatory infiltrate in comparison with the challenged group receiving saline. The compound could lead to reductions in the gingival levels of IL-1β, TNF-α, and MPO (the latter only in the third day) as opposed to the saline control. Furthermore, infliximab treatment reduced the MMP-1/-8, RANK, and RANK-L immunolabeling. Interestingly, a strong RANK-L immunolabeling was found in the ERM during the experimental periodontitis, finding that was diminished by infliximab treatment. Altogether our findings confirm the involvement of the OPG-RANK-RANK-L signaling during the inflammatory osteolytis and the ERM involvement in the experimental periodontitis pathophysiology. In addition, these findings suggest that a local and systemic inflammatory response precedes the activation of that signaling pathway and the bone reabsorption. We conclude that infliximab in the dose of 5.0 mg/Kg had anti-inflammatory and bone protective effect in our experimental periodontal disease in Wistar rats.